"Super stoked girls" - a discourse analysis of girls' participation in freeride skiing. Issue 1 (2nd January 2023) - Malterud, Lotte; Engelsrud, Gunn; Vereide, Vegard
ABSTRACT: This article is based on a selection of Norwegian girls' accounts of backcountry, freeride skiing and mountain biking to better understand how they form and are formed by cultural identity standards. The study is conducted by using the precepts of discourse analysis, which have language and social communication as the central component of the social world. The girls' narratives occupy an ambiguous space that attempts to bridge the gap between their own and other people's perceptions of their identity, gender expression and experience in outdoor adventure sports. Being a skier functions as an anchoring point in their identity formation, binding together incredible experiences out in nature and the recurrent fear of failure. The joy, desire and feeling of freedom in the mountain are challenged by an intense pressure to perform. These ambivalent, sometimes even contradictory experiences are a prominent element of the narrative material produced and analysed in the article.